Calculation of Land and Building Acquisition Duty in Inheritance Land Division - Nur Abadiyah (IAIN Palopo, 2021)
This study aims to determine the calculation of BPHTB which calculates suitability based on Law Number 28 of 2009 and Regional Regulation of Pasuruan Regency Number 2 of 2011. This research was conducted at the Pasuruan Regency Regional Finance and Revenue Management Agency. Data obtained from Notary and PPAT Elisabet Triasnani Widiastuti. The data analysis method used is descriptive quantitative. The results showed that in determining the magnitude of the NPOP value that did not match the magnitude of the NJOP PBB value on certificates of several owners, the NJOP PBB value was first divided using a quantifier/denominator based on the number of names on the certificate. There is a difference in calculating the amount of the NPOP value for several certificate holders of Rp. 97,645,000 which was carried out by the Pasuruan Regency Regional Revenue and Financial Revenue Management Agency is not in accordance with Law no. 28 of 2009 and Regional Regulation of Pasuruan Regency No. 2 of 2011.